THE EFFECTIVENESS OF POP-UP BOOK FOLKTALE STORY IN IMPROVING STUDENTS’ ABILITY IN READING COMPREHENSION (NARRATIVE TEXT MATERIAL) IN NINTH-GRADE SMPN 3 MATARAM - Nurholiza Izzati; Nuriadi, Nuriadi; Kurniawan Apgrianto; Lalu Thohir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to determine the effectiveness of pop-up books in improving the reading ability of class IX students at SMP 3 Mataram in the 2023/2024 academic year. This is an experimental research using a pre-experimental one-group Pre-test-Post-test design. The sample for this research was 30 students in class IX-D of SMP 3 Mataram. The instrument was a test consisting of a pre-test and post-test. The data analysis process was carried out using t-test statistical calculations. The research results show that the t-test are 10.557 and the t-table at the 0.05 confidence level were 2.045, which mean the t-test results are 10.557 higher than the t-table. In other words, the use of pop-up books is effective in improving the reading ability of ninth grade students at SMP 3 Mataram.